Acute variceal bleeding and out-of-hours endoscopy: Evaluation of an emergency care setting according to Baveno VI guidelines adherence. Issue 10 (October 2021) - Alves da Silva, Joana; Falcão, Daniela; Maia, Luís; Guedes, Tiago Pereira; Garrido, Mónica; Novo, Maria Inês; Rocha, Marta; Pinto, Pedro; Moreira, Teresa; Ferreira, José Manuel; Pedroto, Isabel
Abstract: Background: The extent to which patients with acute variceal bleeding (AVB) receive recommended care is largely unknown. Aim: to evaluate the adherence of the 4 major Baveno VI recommendations [vasoactive agents, prophylactic antibiotic, esophagogastroduodenoscopy (EGD) within 12 hours, endoscopic variceal ligation (EVL)] as a marker of quality of an emergency model. Methods: Retrospective evaluation of AVB admissions to a tertiary centre in which endoscopy was available 24hours-a-day, with a regional out-of-hours service at night (the furthest hospital is 200Km away). Patients were divided in directly admitted or transferred from other centres. Results: 210 AVB patients were included; 101 (48.1%) were directly admitted. The majority of patients were submitted to vasoactive agents (85.7%) and prophylactic antibiotics (79%) before EGD. In 178 patients (84.8%) endoscopy was performed within 12h and EVL was the procedure of choice in 116 (74.8%) (only oesophageal varices). No significant differences were observed between directly admitted and transferred patients in adherence rates. Overall rebleeding rate was 8.6%, in-hospital mortality 11.4% and 6-week mortality 20%. Conclusion: Adherence to quality metrics was high which might have played a vital role for reported outcomes. These results suggest that this model of care, provides accessibility and equity in access to urgent endoscopy.